The Double Burden of Malnutrition at the Individual Level Among Adults: A Nationwide Survey in the Philippines - de Juras, Aileen R.; Hsu, Wan-Chen; Hu, Susan C. (Frontiers in Nutrition, 2021)
Introduction: Double burden of malnutrition (DBM) is a fast-evolving public health challenge. The rising prevalence of obesity and diet-related non-communicable diseases alongside persistent nutritional deficiencies are compelling problems in many developing countries. However, there is limited evidence on the coexistence of these conditions in the same individual among community-dwelling adults. This cross-sectional study describes the various forms of DBM and examines the determinants of DBM at the individual level among adults in the Philippines. Materials and methods: A nationwide dataset from the 2013 Philippine National Nutrition Survey was used. The final study sample consisted of 17,157 adults (8596 men and 8561 non-pregnant and non-lactating women). This study focused on three DBM types within adults: (#1) Underweight and at least one cardiometabolic risk factor (Uw + ≥1 CMRF), (#2) Anemia and at least one cardiometabolic risk factor (An + ≥1 CMRF), (#3) Vitamin A deficiency or iodine insufficiency and at least one cardiometabolic risk factor (Other MND + ≥1 CMRF). The total double burden of malnutrition was also evaluated as the sum of the aforementioned three types. Logistic regression models were used to assess associations between socio-demographic and lifestyle factors and DBM. Results: The prevalence of the three types of DBM were: type #1, 8.1%; type #2, 5.6%; type #3, 20.6%, and the total DBM prevalence was 29.4%. Sex, age, educational attainment, employment status, wealth quintile, and alcohol drinking were the risk factors for DBM. In contrast, marital status, smoking, and physical activity were associated with the different DBM types. Conclusion: The study findings contribute to the current state of knowledge on the broad spectrum of individual-level DBM. Understanding the disparities of this phenomenon could guide integrated actions directed to the concomitance of malnutrition in various forms and cardiometabolic disease risks.